2018
DOI: 10.31577/geogrcas.2018.70.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Nové prístupy k hodnoteniu procesu populačného starnutia a ich aplikácia v prípade Slovenska a Európy

Abstract: New approaches to assessing the population ageing process and their application for Slovakia and EuropePopulation ageing is one of the most important phenomenon of the 21st century. This is especially true for the Slovak population. According to almost all population projections and analyzes, the population ageing process of Slovakia will become more dynamic in the next few years. All these studies of population ageing focus on only one characteristic of peopletheir chronological age. Many important characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The Czech Republic is the traditional destination of Slovaks due to their common historical, linguistic, cultural and geographic proximity and favourable regulatory policies among the countries. The number of Slovaks working in Hungary is also estimated to be around 20,000, with more than 13,000 workers commuting to work from Slovakia to Hungary daily (Bolečeková et al, 2018;Šprocha et al, 2018;Vasylieva and Samusevych, 2018). OECD estimates indicated that between 2004 and 2010, on average about 10,000 Czech nationals returned home compared to 13,000 Slovaks and 22,000 Hungarians (Zaiceva and Zimmermann, 2016).…”
Section: Overview Of the Recent Labour Migrations From Czech Republicmentioning
confidence: 99%
“…The Czech Republic is the traditional destination of Slovaks due to their common historical, linguistic, cultural and geographic proximity and favourable regulatory policies among the countries. The number of Slovaks working in Hungary is also estimated to be around 20,000, with more than 13,000 workers commuting to work from Slovakia to Hungary daily (Bolečeková et al, 2018;Šprocha et al, 2018;Vasylieva and Samusevych, 2018). OECD estimates indicated that between 2004 and 2010, on average about 10,000 Czech nationals returned home compared to 13,000 Slovaks and 22,000 Hungarians (Zaiceva and Zimmermann, 2016).…”
Section: Overview Of the Recent Labour Migrations From Czech Republicmentioning
confidence: 99%
“…The short-term goal of the Strategy is to adopt temporary, extraordinary (hot-fix) measures to address the current shortage of skilled labor at Slovak labor market, with a view to later considering the need to maintain the extraordinary measures taken, given the current needs of the labor market or the current number of foreigners in Slovakia (Klamár & Gavaľová, 2018;Sirkeci & Přívara, 2017;Šprocha et al, 2018).…”
Section: Institutional Framework Of the Migration Policy In Slovak Rementioning
confidence: 99%